EFEKTIVITAS E-LKPD BERBASIS PROJECT-BASED LEARNING PADA MATERI KEANEKARAGAMAN HAYATI UNTUK MELATIHKAN KETERAMPILAN BERPIKIR KREATIF KELAS X SMA - Nazwa Salsabila; Ahmad Bashri (STKIP Subang, 2026)
Creative thinking skills are a 21st-century competency that needs to be cultivated. However, instruction on biodiversity tends to remain theoretical, therefore innovation is required in the form of an electronic student worksheet (E-LKPD) based on project-based learning utilizing a herbarium project to foster creative thinking skills. This study aimed to develop an effective PjBL-based E-LKPD on the topic of biodiversity to cultivate the creative thinking skills of 10th-grade high school students. The study employed the ADDIE development model, with a limited trial conducted involving 29 students. The developed E-LKPD integrates PjBL syntax with creative thinking skill indicators. Effectiveness was assessed based on pretest-posttest results, project assessments, and product evaluations. The results showed an average N-gain score of 0.79 (high category), a project score of 89.5%, a herbarium product score of 95%, and an infographic product score of 93.75%, all of which fell into the